Pengaruh Kualitas Layanan dan Kemudahan Penggunaan Terhadap Niat Beli Ulang dengan Kepuasan Sebagai Variabel Mediasi (Studi pada Pelanggan Produk Fashion Melalui Toko Online Zalora) - ROHMATIN, INDA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The purpose of this study is to analyze and discuss the effect of service quality and ease of use on the intention to buy back Zalora fashion products with satisfaction as a mediation variable. The sampling technique used is non-probability sampling with snowball sampling method. The sample used is 220 people. Respondents in this study are consumers who have made their own purchase at least one time purchase on the online store Zalora with a period of 1 month last by the age of 18-25 years. Data analysis using analysis path with AMOS program. The results showed that service quality had positive effect on satisfaction, and ease of use had positive effect on satisfaction. The results of this study also indicate that the quality of service and ease of use has no direct effect on the intention to buy back and through satisfaction as a mediation variable. In the mediation test the quality of service and ease of use proved fully mediated by satisfaction. Keywords: Service quality, ease of use, satisfaction and re-purchase intentions.